Analyzing the Impact of Financial Stability Using the General Aggregate Index Technique for A Sample of Iraqi Private Banks - Karim Sami karim,; Ahmed Hamdi Al husseini, (Technium Social Sciences Journal, 2024)
Studying the state of general financial stability from the perspective of commercial banks and the extent of their application of its indicators is one of the important topics that has received great attention internationally. The problem of the study, which bears the title (Analysis of the impact of financial stability using the general aggregate index technique for a sample of Iraqi banks for the period from 2015 to 2021) is focused on the question: Next: Do commercial banks in Iraq have an impact in achieving financial stability in Iraq if the financial stability rates applied by the Central Bank are applied? The study came in two main parts, the first of which dealt with the theoretical framework of financial stability in terms of the concept, challenges, risks, characteristics and components, while the second dealt with the theoretical framework of financial stability in terms of the concept, challenges, risks, characteristics and components. He touched on showing the extent to which the study sample of commercial banks in Iraq applied financial stability rates through financial analysis of indicators. Thus, the study showed a number of conclusions. One of the most important conclusions was that the state of financial stability in Iraq depends to a large extent in achieving it on commercial banks, which must be developed. And keeping pace with the external environment, other global indicators must be applied, and the position of the commercial banks in the research sample was concluded on the basis of financial analysis, which shows an impact in achieving financial stability.